Is Hope a Good Thing, and Maybe Even the Best of Things? Exploring the Construct of Hope Within the Risk-Needs-Responsivity Model - Duwe, Grant (The prison journal, 2026)
While hope has been found to have beneficial effects across a wide range of pro-social outcomes, there has been limited research on its impact for correctional populations. In June 2024, the Minnesota Department of Corrections incorporated the Adult Hope Scale into its risk-needs-responsivity assessment process. Using data collected on 1,343 individuals incarcerated in Minnesota prisons, the results revealed that greater levels of hope and, in particular, higher scores on the agency dimension were significantly associated with lower recidivism risk. The magnitude of this association was similar to that observed for other criminogenic needs domains, such as anti-social thinking, anti-social peers, and substance use. Although hope did not predict program completion, the agency subscale was significantly and positively associated with involvement in structured activities, which includes education classes, programs, and work assignments. The results suggest that assessing for hope holds the potential to improve outcomes for correctional populations.